PENGEMBANGAN KAWASAN PESANTREN MODERN RAUDHATUL ULUM MERANTI - Sariman, Sariman; Zain, Zairin; Alhamdani, M Ridha; Khaliesh, Hamdil; Putro, Jawas Dwijo (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2021)
Raudhatul Ulum Meranti Islamic Boarding School is a da'wah institution that was established to educate the generation of Muslims in Indonesia, especially in West Kalimantan. Raudhatul Ulum Meranti Islamic Boarding School was founded in 1896 in a village called Meranti Village, Sungai Ambawang District, Kubu Raya Regency. The curriculum applied by the pesantren initially only adhered to the classical system (teaching the yellow book) and developed into a curriculum sourced from the Ministry of Religion (KEMENAG). The aim of developing the area of Raudhatul Ulum Meranti Islamic Boarding School is to make facilities suitable for the modern education system. The design location is on Jalan Muhajirin, Kampung Meranti, Puguk Village, Sungai Ambawang District, Kubu Raya Regency. The stage method in this design starts from the Idea Stage, Data Collection, Analysis, Synthesis, Pre-Design and Design Development. The concept of Natural Pro Rate is applied so the areas that are still green do not have to build by destroying nature in the area, but rather organize and maintain the natural conditions in order to remain green. The results of the development design at Raudhatul Ulum Meranti Islamic Boarding School can make the mosque building as the heart of the area. Worship and educational facilities are made with Islamic nuances by combining ornaments in the building and creating a separate area between the male and female students.